PENGARUH FAKTOR-FAKTOR STRES KERJA TERHADAP KINERJA PENGRAJIN BATIK KUB KEMBANG ASIH, TANJUNG BUMI - S Anugrahini Irawati; Bambang Sudarsono; Faidal Faidal; Anang Ma’ruf (STIE Mahardhika, 2018)
This study discusses the problems that exist in the KUB Kembang Asih Tanjung Bumi. This study consist of five variables: extraorganization factors, organizational factors, group factors, individual factors and performance. The purposes of this study are to determine the effect of the work stress factors consist of the external organization factors, the organizational factors, the group factors and the individual factors on craftsmen performance, partially and simultaneously and which is dominantly effect on it. There are so many work stress factors that effect on craftsmen performance in KUB Kembang Asih. The lack of family support in the external organization as uncertainty wages, and the lack of competitive advantage; the lack of involving the craftsmen in making decision in organizational factors; the lack of time management in group factors; the lack of individual skill to meet delivery in individual factors. Using statistic analysis the results showed that tcount of the external organization factors X1 (3,413), organizational factors X2 (3,968), group factors X3 (2,948) and individual factors X4 (3,281) and the ttable (1.292685). The external organization factors, organizational factors, group factors and individual factors have a significant effect on performance as Fcount 95,673 > Ftable 1,97. And with the value of multiple correlation coefficient R = 0.939 or 93.9%, and than organizational factors become the dominant variable with beta coefficient of 0.343. It can be conclude that the external organization factors, organizational factors, group factors and individual factors effect on performance, partially and simultaneously, and organizational factors dominant influence on the performance.